Preliminary study of the relationship between career choice motivation and understanding of professionalism in newly enrolled medical students in China: a cross-sectional study. Issue 2 (22nd February 2021) - Cui, Xuemei; Ding, Ning; Jiang, Nan; Li, Honghe; Wen, Deliang
Abstract : Objectives: Early professionalism education for first-year students is important for generating sound knowledge and attitudes towards medical professionalism. Of the many factors affecting professionalism and professional identity formation in medical students, career choice motivation is an understudied one. This study aimed to explore the relationship between the career choice motivations of first-year medical students and their understanding of professionalism. Settings and participants: A cross-sectional survey of 940 first-year clinical medicine students was conducted at China Medical University in September 2017 to explore students' motivation to study medicine and its relationship with students' understanding of professionalism. Demographics, career choice motivation and professionalism were obtained through paper questionnaires. Logistic regression analysis was used to analyse the association between career choice motivation and understanding of professionalism while controlling for potential demographic confounders. Results: The most common career choice motivations for first-year medical students (N=843) were interested in the health sciences, income and social status and advocating altruism . The most mentioned subdimensions of professionalism were accountability, pursuit of excellence and compassion . There were significant differences in the understanding of professionalism among students with different career choice motivations. Conclusion: First-year medical students with different motivations to study medicine also have different understandings of professionalism. Medical educators can explore motivations to learning medicine as a new entry point to providing professionalism education for newly enrolled medical students.